CURRENT APPRAISAL OF THE SUITABILITY OF FOOT-AND-MOUTH DISEASE STRAINS IN TWO COMMONLY USED COMMERCIAL VACCINES FOR CONTROL OF FMD IN PAKISTAN - A.Ahmed; A. Latif; R. Zahra; A. B. Zahur2; U. Farooq; A. Ullah; M. Abubakar; A. Jamil; M. Afzal (Journal of Animal and Plant Sciences, 2017)
Vaccination is the primary tool used to control Foot-and-mouth Disease (FMD) in Pakistan. FMD virus mutates regularly in the field and new sub-serotypes continue to emerge. For vaccine to be effective, the vaccine should contain viruses that induce immune response to neutralize the circulating field viruses. This study was undertaken to evaluate if the two commonly used imported FMD vaccines produce sufficient antibodies to neutralize circulating field FMD isolates. Pooled sera from 5 buffalo calves raised against vaccine I and II was used in the serum neutralization test to neutralize 7 field strains of FMD virus serotypes A, O and Asia-1.The field strains of FMD virus were better neutralized with vaccine I than vaccine II. Serotype O and Asia-1 field strains were effectively neutralized with vaccine I antisera. However, low serum neutralization titres were observed against serotype A field isolates suggesting that serotype A strains present in both vaccines need to bebetter matchedwith field strains for effective protection.
Keywords: Foot-and-mouth Disease; vaccines; field strains; vaccine matching; serum neutralization test